A global matchmaking web platform facilitating equitable institutional partnerships and mentorship to strengthen health workforce training capacity - Dykens, J. Andrew; Martin, Keith; Kiguli-Malwadde, Elsie; Kupfer, Linda; Chen, Zhuo (Adam); Reynolds, Nancy R.; Behere, Aniruddh; Bhattarai, Suraj; Peterson, Caryn E.; Weine, Stevan Merill (Frontiers in Education, 2023)
The critical human resources deficit in the healthcare sector in low-resource settings (LRS) has an overwhelming impact on health outcomes and disparities in growth and development of the global healthcare workforce. There is a lack of qualified trainers and mentors and this makes it challenging to connect existing capacity gaps with existing expertise and established programs. Through global health partnerships, training programs, and mentorship, individuals and institutions from around the globe can connect to share training resources and strengthen clinical and research capacity in LRSs. Global health partnerships focused on capacity building face many challenges including; unequal access to information about potential partners and training opportunities, a lack of transparency regarding each institutions training priorities, and inequity and absent reciprocity within global health partnerships that have disproportionate power division between high-resource and LRSs. This initiative, the Consortium of Universities for Global Health Capacity Strengthening Platform (CUGH-CPS) (CUGHCapacityBuilding.org), aims to empower institutions and individuals in LRSs to address these challenges and drive partnership engagement through avenues that are beneficial to the LRS agent needs and context by leading the prioritization of training capacity development across clinical and research domains. The CUGH-CPS helps to identify and create a platform for the dissemination of training and mentorship needs from LRS institutions and share this information with the global community. This manuscript describes this new initiative officially launched to a global audience at the April 2023 CUGH meeting.